Implementasi Asas Keterbukaan dalam Pelaksanaan Program PTSL di Kabupaten Jepara - Hikmawan, Moh Wildan; Adhim, Nur (Fakultas Syariah INSURI Ponorogo, 2023)
Land registration is a process that should be carried out by every community who exercises control over their land, the government seeks various ways to create people who are aware of the importance of registering land under their control with the aim of obtaining legal certainty and legal protection, therefore the government carries out a land registration program complete systematic in Jepara district. This paper aims to explain the implementation of a complete systematic land registration program in Jepara Regency and the implementation of the principle of transparency in the implementation of the PTSL program in Jepara Regency. The research method uses a normative juridical approach that has descriptive characteristics. The results of this study are that the implementation of the PTSL program in Jepara Regency is carried out by the National Land Agency with participation in each village so that the PTSL program is carried out in that village, and also explains the steps in implementing the PTSL program, and solving problems in land disputes and errors in the publication land certificates registered by the community, and the creation of the principle of openness in the PTSL program in Jepara Regency.